Violating the Maxims: A Gricean Analysis of Selected Episodes from Mind Your Language Season 1 (1977) - Abdullah, Bachtiar; Makarim, Raihan Athallah; Perlina, Mia (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This research aims to examine the violation of maxim in the selected episodes of the sitcom Mind Your Language season 1 (1977). The series shows people from different countries with different countries, social backgrounds, religions, and languages learning English as a foreign language in the same classroom taught by Mr Brown. The research method used is descriptive qualitative, using Grice's theory. The researchers analyze the data thoroughly, with observations, to find data results and explanations that will be compiled in conversational dialogue. This study identifies the maxim violations of quality, quantity, relation, and manner in the dialogue between the main characters, Mr. Brown, and the selected students, Maximillian Papandrious, Ali Nadeem, Juan Cervantes, and Giovanni Capello. The study found 3 violations of maxim quality, 14 violations of maxim quantity, 22 violations of maxim relevance and 6 violations of maxim manner.